The Effect Of Internal Environmental Management On The Performance Of Cement Companies In Indonesia With Mediation Green Supply Chain Management Practices - Wayan Rendy Armilando; Iveline Anne Marie; Wahyuningsih Santoso (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The global challenge of preserving the environment, meeting demand, and ensuring corporate sustainability drives the cement industry to implement strategies in its supply chain. The practice of green supply chain management is one of the strategies that are well applied in the face of the challenges to the cement industry. Through the GSCM practical dimension consisting of green manufacturing, green purchasing, green transportation, and green facilities, this research will test the impact of the application of GSCM on the performance of cement companies in Indonesia. The thesis used primary data and obtained 224 respondents from 13 groups of cement companies that are part of the Indonesian Cement Association (ASI). The data were analyzed through descriptive statistics and partial least squares (PLS) techniques using smartPLS software version 3.2.9. Research results show that internal environmental management influences GSCM practices and influences the performance of cement companies in Indonesia. Green purchasing only has a positive impact on operational performance and has no impact on the environmental, economic, or social performance of the company. Green transportation is positive for the economic, operational, and social performances of the enterprise but does not have an impact on environmental performance. The study also found that green supply chain management practices strengthen the relationship between internal environmental management and the performance of cement companies in Indonesia.